Peningkatan Kesadaran Masyarakat Melalui Sosialisasi Peran dan Manfaat Hutan Mangrove: Peningkatan Kesadaran Masyarakat Melalui Sosialisasi Peran Dan Manfaat Hutan Mangrove - Intanurfemi Hismayasari; Hendra Poltak; Ismail Ismail; Ernawati Ernawati; Agung Setia Abadi; Asthervina Widyastami Puspitasari; kadarusman kadarusman; Muhamad Ali Ulat; Yuniar Ayu Hafita; Moejiono Moejiono; Heri Sutanto; Iskandar Iskandar; Syafril Sanusi; Muhammad Idris; Charles Nalle; I Komang H Permana (Politeknik Kelautan dan Perikanan Sorong, 2022)
This activity aims to determine the impact of socialization in increasing knowledge and understanding of the role and benefits of mangroves. The socialization activity was attended by 10 participants using the clasical method and the field practice method. Based on the results of the evaluation, it was found that there was an increase in participants' knowledge and understanding regarding the role and benefits of mangroves from an average of 32% to 95% and could provide the right justification so it is hoped that the increase in knowledge would be accompanied by an increase in public awareness to actively participate in preserving mangrove forests.